The velocity anisotropy of the Milky Way satellite system - Riley, Alexander H.; Grand, Robert J. J.; Pakmor, Rüdiger (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We analyse the orbital kinematics of the Milky Way (MW) satellite system utilizing the latest systemic proper motions for 38 satellites based on data
Gesehen am 31.05.2019